Effect of tomato powder on quality of Chinese sausage - Saksomboon, K.; Meemookich, S.; Kaewsaad, T.; Limroongreungrat, K.; Theprugsa, P. (International Journal of Agricultural Technology, 2020)
Tomato powder is a major source of lycopene, a red coloured pigment with an antioxidant property. It is used for a natural coloring agent in reduced nitrite Chinese sausage. Nevertheless, the levels of tomato powder (0-1.4% w/w) affected the product quality in terms of colour, aw, pH, texture and sensory attributes. Sensory results showed that appearance, taste, texture and overall liking scores of Chinese sausage with 0.2% tomato powder and control treatment were not significantly different (p>0.05). However, residual nitrite of the Chinese sausage with 0.2% tomato powder was less than the control. Product shelf-life was affected by packaging systems (vacuum and non-vacuum packaging) and storage temperatures [ambient (30-32°C) and chilling (4°C) temperature]. The best storage condition of the Chinese sausage with 0.2% tomato powder was performed by vacuum packaging and storage at 4°C that could preserve the Chinese sausage for 12 days.